University students' preferences about savings and investments at individual and national level in the 21st century: The case of Turkey - Aynur Yumurtaci; Bilal Bagis (Review of Economic Perspectives, 2020)
This paper aims to capture the favored both national and individual saving and investment perceptions of the Turkish youth. Also, the research contributes to the understanding of the common preferences of the youth and focuses on perceptions over their home country's saving-investment decisions. We reason, it is important to evaluate views of the youth on national savings and investments as they will be both the decision-makers determining the economic and social policies of the near future and the ones that are directly impacted by these policies implemented today. For this purpose, a questionnaire is applied to randomly selected 550 university students in Turkey and the results are analyzed by the chi-square test. Accordingly, students have mostly preferred that investments should be primarily made to the education sector at national level while investment made for the social security system is placed on the last rank. In addition, education is the most important individual investment choice of participants. On the other hand, information technologies, energy, and agriculture are identified as the most significant investment areas, which could be potentially increased the global competitiveness of their home country. Another important outcome of this research is that students prefer to invest their individual savings in gold and real estate investments, respectively.
Keywords: D6; E2; H3; H5; I3; E52; E62; E63; H31; H32; 330; Economic Policies; Investment; Saving; Turkish Economy; University Students